2015
DOI: 10.1002/pc.23805
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of thermally reduced graphene oxide on the physical and mechanical properties of flexible polyurethane foams

Abstract: Flexible polyurethane (PU) foams were obtained from a two-component system via the one-step method. The foams were modified with thermally reduced graphene oxide added in the amount equal to 0.25, 0.5, and 0.75 wt%. The morphology, static and dynamic properties, and thermal stability of modified foams were determined. The application of carbon filler resulted in the visible increase in the cell size, apparent density, and rigidity of the modified systems, as confirmed by the measurements of glass transition te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Polyurethane foam (PUF) has been widely studied due to its various thermal insulating applications in building construction, liquefied natural gas storage tank and carrier formers, and refrigeration . Another important application is as sound absorber in the design of automobiles, using the acoustic damping abilities of PUF .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethane foam (PUF) has been widely studied due to its various thermal insulating applications in building construction, liquefied natural gas storage tank and carrier formers, and refrigeration . Another important application is as sound absorber in the design of automobiles, using the acoustic damping abilities of PUF .…”
Section: Introductionmentioning
confidence: 99%
“…The use of organoclay lead to the cell size reduction, however, uneven dispersion of the organoclay in the polyol solution was observed. While the incorporation of carbon nanotubes or graphenes in PUF has shown to improve its thermal, electrical, and mechanical properties , studies on their influence on acoustic damping properties are limited . A few studies reported the acoustic damping properties of PUF without correlation to its airflow resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the most efficient and economical way to improve the comprehensive performance of foam materials is through the incorporation of inorganic fillers . It has been reported that the introduction of inorganic fillers, such as montmorillonite, carbon black, kaolinite, graphene oxide, and vermiculite, can significantly improve the mechanical properties and thermal stability of polymer‐based foams.…”
Section: Introductionmentioning
confidence: 99%
“…Rigid polyurethane foams (PUFs) are a unique class of polymers, which have highly crosslinked molecular structures and closed pore structures . Owing to their low thermal conductivity, low weight and good mechanical performance, PUFs have been widely utilized in automotive parts, commercial refrigeration and building engineering fields as lightweight core materials in sandwich structures …”
Section: Introductionmentioning
confidence: 99%